CT60 and +49 polymorphisms of CTLA 4 are associated with ANCA-positive small vessel vasculitis - Kamesh, Lavanya; Heward, Joanne M.; Williams, Julie M.; Gough, Stephen C. L.; Chavele, Konstantia-Maria; Salama, Alan; Pusey, Charles; Savage, Caroline O. S.; Harper, Lorraine (Rheumatology (Oxford, England), 2009)
Objective. To investigate whether single nucleotide polymorphisms (SNPs) within cytotoxic T-lymphocyte antigen-4 (CTLA-4) are associated with ANCA-associated small vessel vasculitis (SVV). Methods. The CTLA-4 CT60 (exon 4), +49 (exon 1) and −318 (promoter region) genotypes were determined by PCR and restriction fragment length polymorphism (RFLP) in 222 white Caucasians of UK origin with SVV and 670 ethnically matched controls. Results. The CTLA-4 exon 1 (+49) and 4 (CT60) polymorphisms are associated with SVV (+49: χ2 = 10.965, P = 0.004; CT60: χ2 = 12.017, P = 0.002). Both disease-susceptible and disease-protective haplotypes have been identified in this cohort, and their frequencies are similar in the subtypes of WG and microscopic polyangiitis. Conclusion. This study provides further evidence that CTLA-4, a susceptibility locus for a number of common autoimmune diseases, may also be involved in the development of ANCA-associated SVV.